2017
DOI: 10.3389/fpsyg.2017.01325
|View full text |Cite
|
Sign up to set email alerts
|

Is Beauty in the Hand of the Writer? Influences of Aesthetic Preferences through Script Directions, Cultural, and Neurological Factors: A Literature Review

Abstract: Human experience surrounding the appreciation of beauty is not static. Many factors such as script direction and cultural differences directly impact whether, how and why we consider images beautiful. In an earlier study, Pérez González showed that 19th-century Iranian and Spanish professional photographers manifest lateral biases linked to reading writing direction in their compositions. The present paper aims to provide a general review on this topic and intends to highlight the most relevant studies reporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
(170 reference statements)
0
10
0
Order By: Relevance
“…Although reading habits have been considered as a main cultural factor in directionality research [4][5][6][7][8][9][10], reading directions do not seem to explain the cultural differences, at least in this perceptual evaluation task. As mentioned in the Introduction section, if one's reading direction enhances the preference for the facing direction that matches this habit, unidirectional English readers would show a larger bias than multidirectional Japanese readers.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Although reading habits have been considered as a main cultural factor in directionality research [4][5][6][7][8][9][10], reading directions do not seem to explain the cultural differences, at least in this perceptual evaluation task. As mentioned in the Introduction section, if one's reading direction enhances the preference for the facing direction that matches this habit, unidirectional English readers would show a larger bias than multidirectional Japanese readers.…”
Section: Discussionmentioning
confidence: 85%
“…However, research has repeatedly demonstrated that an object facing one direction is preferred over the same object facing the opposite direction. Most interestingly, the preferred direction varies considerably across cultures [4] (see for a recent review). In particular, participants' native reading and writing directions have attracted attention [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is now a wide literature that suggests that habitual reading and writing direction (RWD) affects many levels of the cognitive system. At higher levels, besides time and number it can also affect how events [11,12] and sentences describing spatial scenes are represented [13], as well as the aesthetic experience of artists and the public alike [14]. At lower levels, it induces spatial biases in lateral motion perception [15], word reading [16], perceptual span [17], visual exploration [18,19] and spatial attention [20].…”
Section: Introductionmentioning
confidence: 99%